ダイ 28 ジ ナンキョク チイキ カンソク タイ アスカ カンソク キョテン エットウ ホウコク 1987 - 鮎川, 勝; アユカワ, マサル; Ayukawa, Masaru (1989)
P(論文) 第28次南極地域観測隊は, あすか観測拠点における越冬観測の体制を1986年12月18日から1987年2月12日の間に整え, 同年2月20日より8名の隊員編成で初年次越冬観測を実施した。8名のあすか越冬隊員は, 基地の維持, 整備および拡充を実施しつつ, 「東クィーンモードランド地域雪氷・地学研究計画(7年計画6年次)」に基づく南極大陸氷床下の基盤地形および地殻構造に関する研究観測, 「観測点群による超高層物理現象の研究」の一環をなす観測, 「ヒトの生理学的研究」に関する観測などに従事し, 所期の目的を達成した。また, あすか観測拠点での越冬観測開始に伴い, 世界気象機構(WMO : World Meteorological Organization)の規約に基づく地上気象観測を開始し, 国際気象地点番号ASUKA 89524を得た。さらに氷床上の建築物に関するひずみ, ドリフトの生成などの設営的な基礎データ取得のための計測も実施した。本報告は, 日本南極地域観測隊の昭和基地, みずほ基地につぐ第3番目の越冬基地「あすか観測拠点」における初年次の越冬諸活動の概要報告である。 A construction of Asuka Station had been started at the 26th Japanese Antarctic Research Expedition (JARE-26), and all the necessary wintering facilities were finally equipped by mid-February 1987 during JARE-28 operation. The first wintering activities at Asuka Station started immediately thereafter with eight members under the leadership of the present author. Asuka Station is situated at 71°31′S, 24°08′E of 930m a.s.l. The scientific programs consisted of Asuka Station based observations and field and airborne surveys. The observations at Asuka Station were surface observations for meteorological conditions, geomagnetism, earthquake and icequake, gravity earth tide, building strain by snow accumulation, and so forth. The meteorological data were reported to the WMO Data Center twice a day from March 1,1987,under the international index number of 89524. The field surveys were carried out with an airborne magnetometer and iceradar around Sor Rondane Mountains during November and December. The gravity was also measured at every 1km over a span of 160km from the shore Breid Bay to the foot of the Mountains, and the snow accumulation at every 2km. A preliminary survey of terrestrial fauna and flora was also made in the ice free areas of the Mountains. This report gives the details of wintering operations including logistics and a summary of research activities. This publication also includes the information on weather and snowdrift condition around Asuka Station throughout the year. departmental bulletin paper